Climate change and coastal hydrographic response along the Atlantic Iberian margin (Tagus Prodelta and Muros Ría) during the last two millennia - Martín Lebreiro, Susana; Francés, Guillermo; Abrantes, Fátima; Diz, Paula; Bartels-Jónsdóttir, H. B.; Stroynowski, Z. N.; Gil, I. M.; Pena, Leopoldo; Rodrigues, T.; Jones, P. D.; Nombela, Miguel Ángel; Alejo, Irene; et al. (The Holocene, 2006)
13 pages, 6 figures, 2 tables. The Tagus Prodelta (W Portugal) and the Muros Ría (NW Spain) are areas of high deposition rates registering high-resolution palaeoclimatic records for western Iberia. We compare the climatic conditions of the two areas over the last two millennia based on proxies of temperature (sea surface temperatures and oxygen isotopes), continental input (grain size, iron and magnetic susceptibility) and productivity (inorganic and organic carbon, carbon isotopes, benthic foraminifera and diatoms). Biogeochemical changes in the Tagus Prodelta reflect widely recognized North Atlantic climatic periods encompassing the Roman Period (AD 0-350), the Dark Ages (AD 400-700), the ‘Mediaeval Warm Period’ (MWP; AD 800-1200) and the ‘Little Ice Age’ (LIA; AD 1300-1750). The atmospheric North Atlantic Oscillation (NAO) drives the Tagus Prodelta multidecadal, long-term variability in precipitation-river input during cold periods (negative NAO) and marine upwelling during warmer periods (positive NAO), a scheme that is reversed in the Galician region. The Muros Ría shows only local hydrodynamics until AD 1150, including a ‘suboxic’ event in the inner Ría around AD 500-700. Since AD 1150 Atlantic warm upwelled waters have ventilated the outer Ría but only reach the inner Ría at AD 1750. The twentieth-century records are also interpreted as a reflex of the inverse NAO mode in both areas, resulting in amplification of the LIA biogeochemical water conditions. Centennial-scale solar activity appears to be another important forcing mechanism (or the only one, if solar activity drives the NAO and ‘Bond-cycles’) behind changes in the hydrography of the Tagus Prodelta, and primary production, bottom ventilation and organic carbon degradation in the Muros Ría. We are grateful to participants and crews of Discovery 249, Poseidon PALEO 1, and B/O Mytilus cruises, and for laboratory technical assistance in grain size, LECO, isotopes, foraminifera and diatoms at the INETI-Laboratory of Marine Geology. Thanks to C. ...